2005
DOI: 10.1104/pp.104.058958
|View full text |Cite
|
Sign up to set email alerts
|

Virus Induction of Heat Shock Protein 70 Reflects a General Response to Protein Accumulation in the Plant Cytosol

Abstract: Different cytoplasmically replicating RNA viruses were shown to induce a specific subset of heat-inducible heat shock protein 70 (HSP70) genes in Arabidopsis (Arabidopsis thaliana). To identify the inducing principle, a promoter::reporter system was developed for the facile analysis of differentially responding Arabidopsis HSP70 genes, by infiltration into Nicotiana benthamiana leaves. Through transient expression of individual viral cistrons or through deletion analysis of a viral replicon, we were unable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 36 publications
1
90
0
Order By: Relevance
“…Several previous studies have concluded that misfolded proteins induce a subset of the heat-shock response in bacterial (17), fungal (35), plant (13,14), and vertebrate cells (40) by either monitoring transcript or protein changes in response to widespread misfolding (13,35) or monitoring only a handful of heatshock proteins (13,14,17,40). Recent studies have led to the proposal that the UPR-Cyto is a specific HSF1-mediated module of the eukaryotic heat-shock response (13,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have concluded that misfolded proteins induce a subset of the heat-shock response in bacterial (17), fungal (35), plant (13,14), and vertebrate cells (40) by either monitoring transcript or protein changes in response to widespread misfolding (13,35) or monitoring only a handful of heatshock proteins (13,14,17,40). Recent studies have led to the proposal that the UPR-Cyto is a specific HSF1-mediated module of the eukaryotic heat-shock response (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…In the eukaryotic endoplasmic reticulum (ER), misfolded proteins provoke the unfolded protein response (UPR) (11), whereas in the cytosol, a broader heat-shock response combats protein misfolding, oxidative stress, altered membrane integrity, and reduced growth rate (12). Recent work suggests that the heat-shock response may mask a milder and more targeted response to counteract cytosolic protein misfolding (13)(14)(15), dubbed the UPR-Cyto (15), but the molecular components of this response remain unclear.…”
mentioning
confidence: 99%
“…It is well known that a cellular response different from the UPR occurs in the cytosol if protein folding in the cytosol is disturbed. This response is referred to as the cytosolic protein response (CPR) (17), and genes induced in the CPR in Arabidopsis were identified by microarray-excluding genes induced in the UPR (18). However, 30 of 190 genes up-regulated by Tm in ire1a/b were overlapped with the CPR genes, similar to the heat stress-responsive genes (Fig.…”
Section: Up-regulation Of Cytosolic Protein Response Genes In Ire1a/bmentioning
confidence: 99%
“…The Arabidopsis genome encodes five soluble cytosolic HSP70s, HSP70 (referred to as HSP70A in this article) and HSP70B, and three constitutively expressed HSPs, HSC70-1, HSC70-2, and HSC70-3. All of these genes are induced by heat shock treatment, whereas all but HSP70B are induced in the CPR (Aparicio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These are not ubiquitous processes within the cell but are compartmentalized. Hence, the unfolded protein response (UPR), which is induced by the accumulation of misfolded proteins in the endoplasmic reticulum (ER), recruits specific genes and pathways to regulate protein repair in that compartment (Ron and Walter, 2007), and a parallel process, the cytosolic protein response (CPR), operates in the cytosol (Aparicio et al, 2005). Although these processes are essential for maintaining normal cellular function under adverse conditions, how they are integrated into the wider response has been little investigated in higher eukaryotes.…”
Section: Introductionmentioning
confidence: 99%